PENGARUH STRATEGI PEMASARAN TERHADAP VOLUME PENJUALAN PADA PT. RUSDI MEDIKA - Luh Kadek Budi Martini; A.A Istri Ngr. Dyah Prami; Kadek Yashinta Viediantari (Universitas Triatma Mulya, 2022)
The title of the research on the influence of marketing strategy on sales volume at PT. Rusdi Medika. To carry out marketing activities, it must be supported by a marketing strategy commonly referred to as the